Agency and Post-Crisis Resilience: A Qualitative Analysis of Rohingya Women Refugees' Self-Help Capacity Development Strategies in Aceh - Annisah Putri; Ibnu Phonna Nurdin; Cut Maya Aprita Sari; Wais Alqarni; Iqbal Ahmady (Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This study explores the lives of Rohingya women residing in the Minaraya refugee camp, Padang Tiji Subdistrict, Pidie Regency, Aceh, through the lens of the Gender Agency Theory and Resilience Theory. It aims to understand how these women negotiate their roles within a patriarchal social structure and develop resilience amid economic, social, and cultural constraints. The findings reveal that Rohingya women live under a deeply entrenched patriarchal system in which men dominate decision-making processes, while women are confined to domestic responsibilities. However, their compliance should not be interpreted as mere submission; rather, it reflects a form of piety-based agency, a conscious act grounded in religious and moral values to maintain dignity and family harmony. Within the domestic sphere, women play an essential role in managing aid funds, distributing food, and regulating household expenditures. These actions demonstrate adaptive capacity and subtle role negotiation within the limits of gender norms. Spirituality serves as a significant source of strength; religious activities such as Qur'an recitations and collective prayers function as coping mechanisms for dealing with trauma and uncertainty. Furthermore, support from humanitarian organizations helps meet basic needs. However, the core of their resilience stems from family solidarity and deeply held religious values. Rohingya women in Aceh display strength through faith, social adaptation, and resource management, positioning themselves as active agents in sustaining dignity and survival amid adversity.